Prognostic value of basal markers (epidermal growth factor receptor “EGFR” and cytokeratin 5/6) expression in triple-negative invasive breast cancer - Amany Mostafa ElFeky; Eman Mohamed Saied; Hanan Shawky; Emad Sadaka (Journal of the Pakistan Medical Association, 2023)
Objective: The To distinguish between basal and non-basal subtypes of triple-negative breast cancers based on epidermal growth factor receptor and cytokeratin 5/6, and to establish the association of the diagnosis with clinicopathological parameters and survival rates. Methods: The retrospective study was conducted at the Clinical Oncology and Nuclear Medicine Department of Kafrelsheikh University Hospital and Tanta University Hospital, Egypt, and comprised medical records from January 2014 to December 2018 related to cases with histopathologically proven triple-negative breast cancer who had been treated and followed up for at least 5 years. The cases had been evaluated using immunohistochemistry for epidermal growth factor receptor and Cytokeratin 5/6 expression. Data related to prognostic factors, overall survival and diseasefree survival was retrieved. Data was analysed using SPSS 21. Results: There were 100 patients with median age 50 years (inter-quartile range: 35-55.25 years; range: 22-69 years). There were 58(58%) pre-menopausal subjects, 15(15%) had positive family history, and 68(68%) had tumour size T2. Basal markers were noted in 74(74%) patients. Basal subtype was significantly more common in patients aged <50 years at diagnosis, premenopausal women, patients with positive nodal status, those with grade III tumours, and patients with Ki67 proliferation marker >20% (p<0.05). Tumour size, histological subtypes and lympho-vascular invasion were not significantly different between the groups (p>0.05). The basal subtype had worse disease-free survival and overall survival rates (p<0.05). Conclusion: Triple-negative breast cancer patients who expressed epidermal growth factor receptor and/or cytokeratin 5/6 were found to have poor findings, with worse disease-free survival and overall survival. Keywords: Breast neoplasms, Ki67 antigen, EGFR Receptors, Oncology.